2016
DOI: 10.1073/pnas.1608564113
|View full text |Cite
|
Sign up to set email alerts
|

Autotaxin-mediated lipid signaling intersects with LIF and BMP signaling to promote the naive pluripotency transcription factor program

Abstract: Developmental signaling molecules are used for cell fate determination, and understanding how their combinatorial effects produce the variety of cell types in multicellular organisms is a key problem in biology. Here, we demonstrate that the combination of leukemia inhibitory factor (LIF), bone morphogenetic protein 4 (BMP4), lysophosphatidic acid (LPA), and ascorbic acid (AA) efficiently converts mouse primed pluripotent stem cells (PSCs) into naive PSCs. Signaling by the lipid LPA through its receptor LPAR1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 31 publications
3
49
0
Order By: Relevance
“…Fifth, we could not investigate the relationship between CMV infection and possible transcriptional factors for ATX. Several transcriptional factors have been implicated for ATX up-regulation in other cells, including c-Jun and STAT3 (signal transducer and activator of transcription 3) [50][51][52] . We would like to further explore molecular basis for the CMV induced autotaxin upregulation in the trabecular meshwork cells in the future study.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, we could not investigate the relationship between CMV infection and possible transcriptional factors for ATX. Several transcriptional factors have been implicated for ATX up-regulation in other cells, including c-Jun and STAT3 (signal transducer and activator of transcription 3) [50][51][52] . We would like to further explore molecular basis for the CMV induced autotaxin upregulation in the trabecular meshwork cells in the future study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their metabolic roles, lipids may also regulate the primed-to-naïve conversion as a signaling molecule (Kime et al, 2016). Lysophosphatidic acid (LPA) lipid signaling and the LPA-producing enzyme autotoxin have been implicated in establishing naïve PSCs in coordination with LIF and bone morphogenetic protein 4 (BMP4) signaling (Kime et al, 2016). These elegant studies support the importance of nutrient availability for defining stem cell features and suggest that manipulating energy metabolism may be sufficient to promote the transition between stem cell states.…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…Moreover, conditional overexpression of ATX promotes the differentiation of monocytes into macrophages in mice [31]. ATX is also involved in the regulation of the pluripotency transcriptional program, which is mediated by leukemia inhibitory factor (LIF) and bone morphogenetic proteins (BMP) in HSCs [32]. On the other hand, intracellular LPA is synthesized by three enzymes localized in the endoplasmic reticulum (ER) or the mitochondrial membrane: glycerophosphate acyltransferase (GPAT), phospholipase A (PLA), and acylglycerol kinase (AGK) [33][34][35].…”
Section: Lpa Generationmentioning
confidence: 99%
“…In recent years, accumulating studies have revealed the importance of LPA-LPAR signaling in stem cell biology. ATX-LPA axis is reported to regulate the pluripotency of ESCs through the activation of PLC/Ca 2+ signaling and c-myc expression [18,20,32]. LPA receptors have been identified in HSCs, vascular stem cells, bone marrow stromal cells (BMSCs), neurospheres from neural stem cells (NSCs), and embryonic stem cells (ESCs) [53].…”
Section: The Functions Of Lpa In Stem Cellsmentioning
confidence: 99%